Transcription termination factor La is also an initiation factor for RNA polymerase III. - Maraia, R J (1996)
La RNA-binding protein is a transcription termination factor that facilitates recycling of template and RNA polymerase (pol) 111. Transcription complexes preassembled on immobilized templates were depleted of pol III after a single round of RNA synthesis in the presence of heparin and sarkosyl. The isolated complexes could then be complemented with highly purified pol III and/or recombinant La to test if La is required for transcription reinitiation. VA1, 7SL, and B1 transcription complexes cannot be transcribed by supplemental pol III in single or multiple-round transcription assays unless La is also provided. La mediates concentration-dependent activation of pol III initiation and thereby controls the use of preassembled stable transcription complexes. The initiation factor activity of La augments its termination factor activity to produce a novel mechanism of activated reinitiation. A model in which La serves pol III upon transcription initiation and again at termination is discussed.